INVESTIGATION OF THE CONCEPT OF TRIANGLE IN SECONDARY SCHOOL MATHEMATICS TEXTBOOKS IN TERMS OF TOOL/OBJECT DIALECTIC - KİRAZ, Müge; TAPAN-BROUTIN , Menekşe Seden; GÜLER SELEK, Hatice Kübra (SSD Journal, 2023)
In this study, it was aimed to examine the concept of triangle in middle school mathematics textbooks (grades 5-8) in terms of tool/object dialectic and to examine in which case the concept has the status of tool and in which case it has the status of object from the 5th to the 8th grade level. Since the textbooks were analyzed in the study, this study is a document analysis study. The MoNE 5th, 6th, 7th, and 8th grade textbooks taught in middle schools in the 2022-2023 academic year were used as documents in the study. The triangle concept in the textbooks was examined in terms of the tool/object dialectic, and the situations in which the concept is related to the status of tool or object were analyzed using document analysis. As a result of the research, it has been reached that the concept of middle school mathematics 5th grade lesson triangle is mostly in the "object" status, while it is mostly in the "tool" status in the 6th, 7th and 8th grade textbooks. Therefore, it can be interpreted that there are limits to basic learning about triangles in the 5th grade, and that more emphasis should be placed on triangles in the 6th, 7th and 8th grades.